2022
DOI: 10.1186/s12887-022-03516-7
|View full text |Cite
|
Sign up to set email alerts
|

How Covid-19 changed the epidemiology of febrile urinary tract infections in children in the emergency department during the first outbreak

Abstract: Background The first Covid-19 pandemic affected the epidemiology of several diseases. A general reduction in the emergency department (ED) accesses was observed during this period, both in adult and pediatric contexts. Methods This retrospective study was conducted on the behalf of the Italian Society of Pediatric Nephrology (SINePe) in 17 Italian pediatric EDs in March and April 2020, comparing them with data from the same periods in 2018 and 2019. The total number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…Our results are in concordance with another study from a community setting [2]. However, according to other hospital-based studies, children requiring hospitalization due to UTI were not affected when compared to other diseases like respiratory tract infections, which are transmitted through the same route as SARS-CoV-2 [10]. Some studies evaluating the effect of the pandemic on UTI in community settings have shown decreased prevalence [15].…”
Section: Frequency Of Utisupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are in concordance with another study from a community setting [2]. However, according to other hospital-based studies, children requiring hospitalization due to UTI were not affected when compared to other diseases like respiratory tract infections, which are transmitted through the same route as SARS-CoV-2 [10]. Some studies evaluating the effect of the pandemic on UTI in community settings have shown decreased prevalence [15].…”
Section: Frequency Of Utisupporting
confidence: 90%
“…Antimicrobial resistance is a silent epidemic that got a boost during the pandemic. There are several studies evaluating the impact of the pandemic on UTI and antimicrobial resistance [9][10][11]. With increased awareness about antimicrobial stewardship, most hospitals are shifting to the rational use of antibiotics and updating their antibiogram periodically [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier investigations have noted either decreased or unchanged rates of UTI during the pandemic compared with prepandemic trends . However, these studies were limited to select settings of care (eg, outpatient only, inpatient pediatrics at only university-affiliated sites, US hospitals, and international hospitals).…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier investigations have noted either decreased or unchanged rates of UTI during the pandemic compared with prepandemic trends. 16 , 18 , 19 , 20 , 21 , 22 However, these studies were limited to select settings of care (eg, outpatient only, 16 inpatient pediatrics at only university-affiliated sites, 18 , 19 US hospitals, 16 , 18 , 19 and international hospitals 20 , 21 , 22 ). Additionally, because these studies focused on numerous conditions, they did not use comprehensive lists of diagnosis codes, did not require evidence of antibiotic treatment for the definition of UTI, and did not examine severity measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation